School gardens and biofertilization as a strategy towards climate change mitigation and adaptation in Costa Rica - Rojas Alvarado, Carlos (2021)
School gardens are important for the conceptual integration of topics such as climate change. Using a biofertilization experiment in a school garden, we evaluated four experimental treatments and the student knowledge to some sustainable practices. Solid biofertilization was more effective than liquid treatments. The effect of the garden establishment was positive on the knowledge demonstrated by students. Similar activities are recommended in the context of primary education in Costa Rica.